Physico-chemical Parameters of Parthenium from Morshi Region, Part-I - Dhakite, S.P.; Tayade, D.T. (Asian Journal of Chemistry, 2010)
Parthenium possesses harmful and useful properties in the same plant. Therefore it appeared sufficiently interesting when from 1st July 2001 to 30th September 2001 in the Morshi region we undertook a programme to explore the chemistry of parthenium by analysing some of its physico-chemical parameters, viz., percentage of moisture, as content, solubility in cold and hot water, NaOH and HCl, and its flowers and leaves.